Engineered Nanopore of Phi29 DNA-Packaging Motor for Real-Time Detection of Single Colon Cancer Specific Antibody in Serum - Wang, Shaoying (2013)
The ingenious design of the bacterial virus phi29 DNA packaging nano-motor with an elegant and elaborate channel has inspired its application for single molecule detection of antigen/antibody interactions. The hub of this bacterial virus nanomotor is a truncated cone-shaped connector consisting of twelve protein subunits. These subunits form a ring with a central 3.6-nm channel acting as a path for dsDNA to enter during packaging and to exit during infection. The connector has been inserted into a lipid bilayer. Herein, we reengineered an Epithelial Cell Adhesion Molecule (EpCAM) peptide into the C-terminal of nanopore as a probe to specifically detect EpCAM antibody (Ab) in nano-molar concentration at the single molecule level. The binding of Abs sequentially to each peptide probe induced step-wise blocks in current. The distinctive current signatures enabled us to analyze the docking and undocking kinetics of Ab-probe interactions and determine the K(d). The signal of EpCAM antibody can be discriminated from the background events in the presence of non-specific antibody or serum. Our results demonstrate the feasibility of generating a highly sensitive platform for detecting antibodies at extremely low concentrations in the presence of contaminants.